Distributed, ambient, and pervasive interactions : third International Conference, DAPI 2015, held as a part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, proceedings /: third International Conference, DAPI 2015, held as a part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, proceedings. (2015) - Unknown
No abstract available